Jude - Winterbottom, Michael (2004)
Jude Fawley (Christopher Eccleston) is a stonemason who loves learning. Inspired by his teacher he longs to go to University. After a brief but unhappy marriage to the daughter of a local pig farmer, he moves to Christminster to be closer to his beloved scholars. There, he meets and falls totally in love with his cousin sue Bridehead (Kate Winslet), a thoroughly modern young woman, whose wit and beauty captive him, The Ill-fated lovers join in an illicit union that flount society's conventions and tragedy ensues